Can emotion regulation difficulty lead to adolescent problematic smartphone use? A moderated mediation model of depression and perceived social support. (January 2020) - Fu, Linqian; Wang, Pengcheng; Zhao, Meng; Xie, Xin; Chen, Ye; Nie, Jia; Lei, Li
Highlights: ERD is positively related to PSU. Depression mediates the link between ERD and PSU. Perceived social support moderates the link between depression and PSU. Abstract: Prior studies have identified some risk factors for problematic smartphone use. However, little research has examined the potential influence of emotion regulation difficulty on problematic smartphone use, and less is known about the mediating and moderating mechanisms behind this relationship. This study examined whether emotion regulation difficulty would be related to adolescent problematic smartphone use, whether depression would mediate the relationship between emotion regulation difficulty and problematic smartphone use, and whether perceived social support would moderate the links between emotion regulation difficulty and problematic smartphone use. A total of 720 Chinese adolescents (mean age = 13.66 years, SD = 1.36) completed anonymous questionnaires regarding depression, emotion regulation difficulty, perceived social support, and problematic smartphone use. The results indicated that emotion regulation difficulty was positively related to problematic smartphone use and depression mediated this relationship. Moderated mediation analyses showed that the pathway between depression and adolescent problematic smartphone use was moderated by perceived social support. These findings highlight the significance of identifying the mechanisms that moderate the mediated paths between emotion regulation difficulty and adolescent problematic smartphone use.